Enhancing Compliance and Policy Management for Global E-Commerce Marketplaces - Vinay Acharya (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Global e-commerce marketplaces face an increasingly complex regulatory environment as they expand across jurisdictions. Compliance and policy management have become crucial for ensuring seamless operations, fostering trust, and avoiding penalties. This paper delves into the evolution of e-commerce regulations, technological enablers, and the strategic frameworks essential for managing compliance at scale. By exploring the challenges of regulatory fragmentation, data privacy, intellectual property, and taxation, we propose scalable, AI-driven solutions and harmonized global best practices to enable efficient policy management. Insights into emerging trends and ethical considerations further illustrate how compliance can align with business objectives and consumer trust.